Answer:
Explanation:
![2x^2+4x-30=0\\<=> x^2+2x-15=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/4sj0zeu7zg0b8y9ihpoppgzq34rtxd9zv7.png)
so we know that the sum of the two solutions is -2 and the multiplication -15
so we are looking for x so that
x+3=-2 and 3x=-15
it gives x = -5
another way to do it is to put (x-3) in factor as we know that 3 is one of the solutions it gives
![2x^2+4x-30 = 2(x-3)(x+5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/xfco56jv6f2tg4yfinl11kwzxkdjucbiic.png)
and then the second solution is -5